Analysis of Occupational Health and Safety Risks in the Surgical Inpatient Room at Hospital - Siti Mariam; Agung Aji Perdana; Riyanti Riyanti; Khoidar Amirus; Fitri Eka Sari (Postgraduate, University of Mataram, 2023)
According to the latest report from the International Labor Organization, more than 1.8 million people died in Asia-Pacific. At the Asian level, as many as two-thirds of the global population of more than 2.78 million people die every year due to work accidents or occupational diseases. Meanwhile, based on the National Safety Council (NSC) report, it shows that 41% of accidents in hospitals are greater than in other industries. . The purpose of this study was to determine the level of occupational safety and health risks in the surgical inpatient room of X Hospital Bandar Lampung. This study uses a semi-quantitative method that refers to AS/NZS: 2004 and a method for identifying risk using job hazard analysis (JHA) and multiplying the values​​of consequence, likelihood, exposure to determine the level of risk. The research results obtained with a substantial risk level of 1 risk and an acceptable level of 10 risks.